1991
DOI: 10.1128/mcb.11.6.3043
|View full text |Cite
|
Sign up to set email alerts
|

The Steel/W transduction pathway: kit autophosphorylation and its association with a unique subset of cytoplasmic signaling proteins is induced by the Steel factor.

Abstract: The Wlc-kit and Steel loci respectively encode a receptor tyrosine kinase (Kit) and its extracellular ligand, Steel factor, which are essential for the development of hematopoietic, melanocyte, and germ cell lineages in the mouse. To determine the biochemical basis of the SteeliW developmental pathway, we have investigated the response of the Kit tyrosine kinase and several potential cytoplasmic targets to stimulation with Steel in mast cells derived from normal and mutant W mice. In normal mast cells, Steel i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(125 citation statements)
references
References 59 publications
5
119
1
Order By: Relevance
“…The data presented here imply major di erences between the isoforms in their interaction with signal transducing molecules. It will be important to investigate their interactions with phosphatases such as SHP-1 which is associated with c- KIT (Yi and Ihle, 1993) and a range of proteins such as Shc (Matsuguchi et al, 1994), Tec (Tang et al, 1994), Lyn , PLCg1 (Rottapel et al, 1991;Herbst et al, 1995b), p120 CBL (Wisniewski et al, 1996), JAK2 (Weiler et al, 1996) and Stat 1 that are known to be recruited or activated on SLF binding to c-KIT.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented here imply major di erences between the isoforms in their interaction with signal transducing molecules. It will be important to investigate their interactions with phosphatases such as SHP-1 which is associated with c- KIT (Yi and Ihle, 1993) and a range of proteins such as Shc (Matsuguchi et al, 1994), Tec (Tang et al, 1994), Lyn , PLCg1 (Rottapel et al, 1991;Herbst et al, 1995b), p120 CBL (Wisniewski et al, 1996), JAK2 (Weiler et al, 1996) and Stat 1 that are known to be recruited or activated on SLF binding to c-KIT.…”
Section: Discussionmentioning
confidence: 99%
“…SCF treatment is known to increase cytoplasmic calcium levels (34) and to stimulate the phosphorylation of the components of c-KIT-associated signaling pathways (35,36). Since SCF effects are modulated by PKC (30,37), the role of PKC in RAFTK stimulation was investigated.…”
Section: Scf Induces the Tyrosine Phosphorylation Of Raftk In Cmk Megmentioning
confidence: 99%
“…Cytoplasmic proteins involved in mitogenic pathways have been largely described for KIT, FMS and FLT3, [30][31][32][33][34]60,61 although few of them were reported to be involved in a pathway common to all three RTK. Mutated receptors, deficient in different substrate binding sites, will be useful in the description of such pathways.…”
Section: Figurementioning
confidence: 99%
“…Both KIT and PDGF␤-R are associated with PLC␥ and PI3Ј kinase, whereas FLT3 shows an association with PI3Ј kinase only. [30][31][32][33]63,64 In this study, we showed that FLT3 is unable to promote adhesion of mast cells to a fibronectin matrix. It is not known whether this results from either the lack of PLC␥ activity or from the different location, at the C-terminus sequence of the SH2-p85-PI3Ј kinase binding site (Tyr 958) of FLT3 64 compared to other class III RTK.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation